Environmental and economic implications of electronic waste (e-waste) in Malaysia / Mawardi Omar ... [et al.] - Omar, Mawardi; Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Syaziayani; Syed Abdullah, Sharifah Sarimah (Unit Penerbitan JSKM, 2025)
As one of the fastest-growing waste streams globally, e-waste presents significant challenges and opportunities for developing economies. The research highlights how Malaysia's rapid technological advancement and urbanization have contributed to increased e-waste generation, while regulatory frameworks remain inadequately implemented. The environmental implications include soil and water contamination, air pollution, increased carbon footprint, and threats to biodiversity due to hazardous substances like heavy metals. From an economic perspective, e-waste contains valuable recoverable materials that could contribute to resource security and economic resilience. The study also discusses how proper e-waste management creates employment opportunities and stimulates entrepreneurship. However, low recycling rates persist due to inadequate infrastructure and limited public awareness. The paper concludes that improving regulatory enforcement, enhancing public education, and investing in sustainable recycling infrastructure are essential steps toward creating an e-waste management system that effectively balances environmental protection with economic development.